2019
DOI: 10.1002/jclp.22793
|View full text |Cite
|
Sign up to set email alerts
|

The link between sleep disturbances and suicidal thoughts and behaviors in remitted bipolar I patients

Abstract: Objective We aimed to evaluate the links between different sleep parameters and suicidal ideation and behavior in remitted bipolar I patients. Methods One hundred eight remitted bipolar I patients were recruited from the psychiatry department of Razi Hospital. The third item of the “Hamilton Depression Rating Scale” was used to evaluate current suicidal behaviors. Circadian typology, daytime sleepiness and sleep quality were evaluated using the “Horne and Ostberg Morningness‐Eveningness Questionnaire,” the “Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“… 15 , 23 , 24 , 25 , 26 The prevalence of sleep quality in our study (48.7%), is lower than those of existing studies in similar euthymic patients (56.5% – 82.9%). 23 , 27 , 28 Methodological differences could have accounted for the lower prevalence observed in our study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“… 15 , 23 , 24 , 25 , 26 The prevalence of sleep quality in our study (48.7%), is lower than those of existing studies in similar euthymic patients (56.5% – 82.9%). 23 , 27 , 28 Methodological differences could have accounted for the lower prevalence observed in our study.…”
Section: Discussionmentioning
confidence: 65%
“…15,23,24,25,26 The prevalence of sleep quality in our study (48.7%), is lower than those of existing studies in similar euthymic patients (56.5% -82.9%). 23,27,28 Methodological differences could have accounted for the lower prevalence observed in our study. We found that a significantly higher proportion of the participants who had poor sleep quality were single or never married compared to those with good sleep quality.…”
Section: Discussionmentioning
confidence: 65%